Cities Cultural Heritage Resilience versus the Urban Web Development. Case Study: The City of Athens - Cheirchanteri , Georgia (MAJ - Malaysia Architectural Journal, 2025)
Tangible cultural heritage management is addressed to all planning levels starting from the building and ending up the city itself. Especially the management of cities cultural heritage has to take into account the urban space factors and conditions in an effort to ensure the cultural legacies resilience. Resilience, sustainability and cultural heritage are conceptually linked with the city space. Cultural heritage itself can be a cause and a starting point for enhancing the resilience and sustainability physiognomy of a city. Strengthening the resilience of urban heritage must refer to its integrated management, aiming at the protection, restoration and promotion of monuments, through conservation, adaptation and development. The city of Athens is a modern metropolis with a strong historical past and cultural background. The urban transformations that have taken place following important historical events have given the current form of the city in the whole of ​​which there are many monuments and buildings of architectural interest. The problems that prevail in the urban public space as well as the environmental and socio-economic conditions make the cultural elements vulnerable, often threatening their integrity and generally their resilience. The urban heritage management of Athens must consider the city as a set of processes and systems. Based on the resilience concept they must aim not only at the cultural heritage preservation but also at the adaptation to each period data and challenges. The public space and the buildings located in the Athens area, are considered a direct means of communication for visitors and city residents, who are important both to interact with the space and participate in the cultural heritage management and use.